Basic research on usefulness of convolutional autoencoders in detecting defects in concrete using hammering sound. (July 2023) - Sonoda, Yoshimi; Lu, Chi; Yin, Yifan
Because hammering sound tests are inexpensive and can be performed easily, they are commonly used as an inspection method for examining the presence of defect areas (voids or peelings) in aged concrete structures. However, the evaluation of the health of concrete using hammering sounds depends on the subjective experience of the inspector. Therefore, there is a demand to develop a highly reliable and objective diagnostic method that is accurate and efficient. In this study, we used a convolutional autoencoder (CAE) to develop a diagnostic method that could assist the inspectors with quantitative diagnostic results of tapping sound when detecting defect areas in concrete. In particular, we verified the anomaly detection accuracy of hammering sound data of actual bridges that have deteriorated over time using the proposed CAE model.